Chemical Vapor Deposition of Thin, Conductive, and Fouling-Resistant Polymeric Films - Wang, Minghui (Langmuir : the ACS journal of surfaces and colloids, 2017)
Fouling has been a persistent issue within applications ranging from membrane separation to biomedical implantation. Research to date focuses on fouling-resistant coatings, where electrical conductivity is unnecessary. In this study, we report the synthesis of multifunctional thin films with both fouling resistance and electrical conductivity for their potential applications in the electrolysis-based self-cleaning of separation membranes and in the field of bioelectronics. This unique combination of properties results in multifunctional coatings that are a zwitterionic derivative of intrinsically conductive polymer poly(3,4-ethylenedioxythiophene) (PEDOT) synthesized via oxidative chemical vapor deposition (oCVD). Their fouling resistance is shown to be comparable to that of known dielectric fouling-resistant surfaces, such as a poly(4-vinylpyridine)-co-divinylbenzene (p4VP-DVB)-derived zwitterionic coating, an amphiphilic poly(1H,1H,2H,2H-perfluorodecyl acrylate-co-2-hydroxyethyl methacrylate) (pPFDA-HEMA) coating, and a glass surface, and are far superior to the fouling resistance of gold or polydimethylsiloxane (PDMS) surfaces. The fouling resistances of seven surfaces are quantitatively characterized by molecular force probe (MFP) analysis. In addition, four-point probe electrical measurements, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), variable-angle spectroscopic ellipsometry (VASE), profilometry, water contact angle (WCA) measurements, surface ζ-potential measurements, and atomic force microscopy (AFM) were employed to characterize the physiochemical properties and morphology of the different surfaces